Nurse work stress causative factors during the new normal period of COVID-19 outbreak in D.I Yogyakarta Province - Maryana Maryana; Sari Candra Dewi; Abiyyu Naufal Susanto; Aga Rahma Putri; Ayunda Sekar Arum; Titik Fajriyati Nur Khasanah (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2021)
The prevalence of cases Covid-19 in the New Normal period is still high in the number, that matter affects nurses of work stress. These situations can affect the physical and mental health of nurses. This study aims to determine the relationship of demographic factors and factor additional stress during COVID -19 outbreaks with stress levels of nurses working on the new normal period COVID -19 in the Special Province of Yogyakarta. This type of study was descriptive correlative that aims to determine the relationship of demographic factors with the level of work stress nurses with applied a cross-sectional study design. The study located in the Yogyakarta Special Region Province with the implementation time started on July 1 - July 31, 2020. The samples of this study were clinical nurses who working in health care facilities during the new normal COVID-19 period in the Special Province of Yogyakarta. There were 595 nurses who sampled in this study. The Data collection techniques in this study were directly from the data source using an online questionnaire. . The further results of the research found that there are several factors that influence the work stress of nurses during new normal COVID-19 such as gender, type of health work facility in covid-19 pandemic era, types of nurses in handling covid-19 patients, and length of work (?=1.00). Besides other factors that also influence among them are age (?=0.06), level of education (?=0.40), and work units during the covid-19 pandemic(?=0.89). In order to reduce stress levels, nurses in the COVID-19 new normal era should promote self-evaluation, improve positive coping mechanisms, and improve the good quality of communication techniques in interpersonal relations, so that will facilitate the implementation of daily tasks that ultimately establish good cooperation to complete the task.